Cryogenic Hard Turning of ASP23 Steel Using Carbon Dioxide. (2015) - Pereira, O.; Rodríguez, A.; Fernández-Valdivielso, A.; Barreiro, J.; Fernández-Abia, A.I.; López-de-Lacalle, L.N.
Abstract: Due to rising worldwide industrial competitiveness the machining sector is compelled to improve day by day. In this way, CO2 cryogenic machining is presented as alternative to conventional hard turning. So, in the tests carried out in this research, dry and CO2 cryogenic hard turning with two types of inserts were compared. The variables measured were tool life, superficial roughness and the piece microstructure. The results show an increase of tool life over 60%, a similar superficial roughness and, when positive insert is used, the absence of the white layer.